Lazy Wave Flexible Riser Dynamic Tension Analysis with Variation of Diameter and Buoyancy Module Configuration in Extreme Condition - Muhammad Farhan; Eko Budi Djatmiko; Murdjito (International Journal of Offshore and Coastal Engineering, 2025)
ABSTRACT Oil and Gas Production at floating offshore facilities is growing. It prompted the design of the Flexible Riser as a solution to channel exploration results to floating offshore facilities. In this final project, dynamic stress analysis of lazy wave flexible riser is carried out with variations in diameter and number of buoyancy modules under extreme conditions. This study discusses the maximum tension and minimum bending radius (MBR) on the flexible riser due to variations in diameter and number of buoyancy modules in extreme conditions with two system conditions, namely intact conditions and damage conditions. From the results of the analysis, the larger the diameter of the flexible riser, the greater the maximum tension at the SPM point. While it will be smaller at the PLEM point and the more buoyancy modules used, the smaller the maximum tension at the SPM point, the larger it will be at the PLEM point. The larger the diameter of the flexible riser, the smaller the MBR in the SagBend area. The larger the HogBend area and the more buoyancy modules used, the larger the MBR in the SagBend area, while the smaller the HogBend area.